2015
DOI: 10.1016/j.compbiomed.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical implications of excessive endograft protrusion into the aortic arch after thoracic endovascular repair

Abstract: Endografts placed in the aorta for thoracic endovascular aortic repair (TEVAR) may determine malappositioning to the lesser curvature of the aortic wall, thus resulting in a devastating complication known as endograft collapse. This premature device failure commonly occurs in young individuals after TEVAR for traumatic aortic injuries as a result of applications outside the physical conditions for which the endograft was designed. In this study, an experimentally-calibrated fluid-structure interaction (FSI) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Also, no proven and shared values for the grading of these features are available. In our review, a threshold value for the α angle was not suggested in any article, and only 5 clinical studies 1,[16][17][18]28 and 1 experimental work 39 reported a threshold value for the PLS. No further studies, however, were performed to validate these findings.…”
Section: Discussionmentioning
confidence: 94%
“…Also, no proven and shared values for the grading of these features are available. In our review, a threshold value for the α angle was not suggested in any article, and only 5 clinical studies 1,[16][17][18]28 and 1 experimental work 39 reported a threshold value for the PLS. No further studies, however, were performed to validate these findings.…”
Section: Discussionmentioning
confidence: 94%
“…The implantation of a stent-graft brings about changes in the biomechanical properties of the stented thoracic aorta, and the compliance mismatch between the stented and non-stented regions can have consequences on stress and strain distributions. 7 Also, patient-specific anatomical features can play an important role in determining stress distribution and the location at high risk of tear formation. In this case study, a much wider arch and a longer and more tortuous aorta was observed in the SINE patient (Patient 1), especially in the stent region.…”
Section: Discussionmentioning
confidence: 99%
“…To study the correlation of shear stress with the morphological features, computational flow analyses were developed, according to our previously developed approach [21,[26][27][28][29][30][31][32][33][34]. Hemodynamics were studied at the peak systole, with the aortic valve at the fully opened configuration.…”
Section: Strain and Flow Analysismentioning
confidence: 99%